2020
DOI: 10.1371/journal.pone.0227868
|View full text |Cite
|
Sign up to set email alerts
|

Association of cataract and sun exposure in geographically diverse populations of India: The CASE study. First Report of the ICMR-EYE SEE Study Group

Abstract: PurposeTo determine the prevalence of cataract and its association with sun exposure and other environmental risk factors in three different geographically diverse populations of India. DesignPopulation based cross sectional study during ParticipantsPeople aged � 40 years residing in randomly sampled villages were enumerated (12021) and 9735 (81%) underwent ophthalmic evaluation from plains, hilly and coastal regions (3595, 3231, 2909 respectively) MethodsA detailed questionnaire-based interview about outdoor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Our study result is consistent with many previous studies regarding the association of sunlight exposure and the incidence of cataracts [13][14][15]. This result demonstrates the importance of protecting people's eyes from direct sunlight exposure, especially for those who need to work under sunlight exposure, such as farmers, fishermen, construction workers, etc.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study result is consistent with many previous studies regarding the association of sunlight exposure and the incidence of cataracts [13][14][15]. This result demonstrates the importance of protecting people's eyes from direct sunlight exposure, especially for those who need to work under sunlight exposure, such as farmers, fishermen, construction workers, etc.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the previous studies have demonstrated that sunlight exposure is a significant risk factor for cataracts. For examples, a population-based cross-sectional study on the prevalence of cataract and its association with sun exposure in three different geographically diverse populations of India during 2010-2016 has reported that cataract is associated with an increased sun exposure level [13].…”
Section: Sunlight Exposurementioning
confidence: 99%
“…Therefore, it is highly plausible that solid fuel smoke can also deposit on the eyes and alter the chemical equilibrium and immunity of the tear film, thus increasing the risk of infection and damaging ocular cells directly [2]. The free radicals in solid fuel smoke may accelerate the oxidation of the lens leading to cataracts [46]. Carbon monoxide, another prominent pollutant generated from incomplete combustion of solid fuels, may harm the eyes through hypoxia [47].…”
Section: Plos Medicinementioning
confidence: 99%
“…Different risk factors were implicated with some patients. In a study conducted in western India to investigate the risk factors for the early onset of cataracts in India by Vashist et al, atopy was found to be the most common risk factor associated with cataract formation, being associated with 25.6% of cases [18] . A higher correlation of cataracts with DM was found in our research.…”
Section: Discussionmentioning
confidence: 99%